2016
DOI: 10.1590/s0102-865020160060000004
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase ameliorates matrix metalloproteinase-9 to promote lipopolysaccharide-induced acute lung injury in mice 1

Abstract: PURPOSE:To investigate the regulatory roles of neutrophil elastase (NE) and matrix metalloproteinase-9 (MMP-9) in lipopolysaccharide (LPS)-induced acute lung injury (ALI) in mice. METHODS:To construct LPS-induced ALI mouse models, wild-type C57BL/6 mice were administered 5.0 mg/kg of LPS through endotracheal, and/or 1.0 mg/kg of ONO-5046, and/or 20.0 mg/kg of chemically modified tetracycline-3 (CMT-3) by gavage. The levels of MMP-9, tissue inhibitor of metalloprotease-1, interleukin (IL)-6 were detected by rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“… 22 Moreover, NE can cooperate with MMPs and amplify the effect of ECM degradation. 23 In addition to matrix degradation, NE can also promote peri-bronchial fibrosis by enhancing fibroblast proliferation. 24 Moreover, NE is a potent stimulant of mucus secretion from submucosal glands and goblet cells, which are involved in airway obstruction.…”
Section: Introductionmentioning
confidence: 99%
“… 22 Moreover, NE can cooperate with MMPs and amplify the effect of ECM degradation. 23 In addition to matrix degradation, NE can also promote peri-bronchial fibrosis by enhancing fibroblast proliferation. 24 Moreover, NE is a potent stimulant of mucus secretion from submucosal glands and goblet cells, which are involved in airway obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found that BALF NE significantly increased following OALT, which was closely related to the filtration of neutrophils, suggesting that NE may act as a mediator during neutrophil infiltration-related lung injury during LT. Similarly, a recent study also found that NE promoted ALI induced by lipopolysaccharide stimulation, which may be related to a mechanism of matrix metalloproteinase-9 reduction [28]. Furthermore, our results showed that neutrophil infiltration and NE release contributed to pulmonary barrier dysfunction via aggravating lung oxidative stress, similar to the findings of Aoshiba et al, which showed that the treatment of bronchial epithelial or lung fibroblast cells with the serine protease NE increased mitochondrial and cytoplasm ROS levels [29].…”
Section: Discussionmentioning
confidence: 90%
“…Intriguingly, we also observe significant up-regulation of ELANE , the neutrophils’ elastase, in these patients. ELANE has not only been reported to directly interact with MMP9 [18] , but also to be linked to a higher risk of neutropenic patients to develop AML when its content is lower than normal [19] . Notably, COL24A1 has also been recently found to have a prognostic value in cancer [20] , though this is the first time it is associated to AML.…”
Section: Discussionmentioning
confidence: 99%